DUE TO LAW OF SELECTING THE RIGHT REPUDIATION CITIZENSHIP STATUS IN CITIZENSHIP LAW REVIEW OF INDONESIA - Qurrotul Uyun (JARES (Journal of Academic Research and Sciences), 2019)
Designation (naturalization) includes giving Indonesian citizenship status of one or a number of people from foreign nationals, or gives the status as a citizen of Indonesia or the number of people who do not have citizenship (stateless) .According to the laws of the Republic of Indonesia citizens who have dual citizenship must choose one of these citizenship so until he has only one nationality. For Indonesian citizens are treated when these approvals to those Indonesian nationals, according to Indonesian citizenship legislation that called "gain" or "select" nationality of the Republic of Indonesia will be replaced with Indonesian nationality, and which are called "retained" Dutch nationality or nationality of foreign countries or "reject" Indonesian nationality. So goes the Indonesian nationality, if it has lost the nationality Indonesia automatically all matters concerned with the rights and obligations of citizens or her country also erased or lost. The problem that will be discussed are: Does the right of repudiation in the process of selecting citizenship status lead to legal consequences for those concerned? Does repudiation rights used in the process of selecting citizenship status in Indonesia? By studying this research, it is expected to find out the point of problems in selecting indonesian citizenship.This research used qualitative. Since this method is a directed and systemic method. In addition, this research study used statute approach and conceptual approach. It is an approach which comes from views and doctrines that are developed in the science of law.The findings of this research are: first, as a result of law that is rejected, rejected state has no right to force someone to reject the offer, this happens because of self-will without intervension from other sides. Since, the status of citizenship related to the existence in getting right and obligation of someone in every action. The second problem is repudiation right that is used in Indonesia by special naturalization. It means that the state is able to offer or give citizenship status by using it, and in this session, the citizen has right to receive or reject that offer.